Column: Black Woman Health - Gender and race institutional discrimination. How the nurse can prevent these violations? - Isabel CF da Cruz (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
The gender aspects of racial discrimination and the racial aspects of gender
discrimination must be included in the healths disciplines. Intersectionality is a feminist approach to combat gender and race discrimination. This column highlight key issues related to prevent and/or combat institutional racism in the health system.